PENGALIHAN HAK ASUH ANAK KEPADA AYAH SEBAB PERCERAIAN DI PENGADILAN AGAMA MEMPAWAH; STUDI PUTUSAN NOMOR 343/Pdt.G/2016/PA Mpw DALAM PERSPEKTIF MASLAHAH - ., Miskari; Gunawan, Hendra (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
The purpose of this article research is to find out the problems behind the ownership of Child Custody to the father in the case decision Number: (343/Pdt.G/2016/PA Mpw). In this study, researchers chose the object of research on the decision of the Mempawah Religious Court. Researchers want to know the problems that allow the delegation of children's rights to their biological fathers as a result of the divorce of husband and wife. In addition, the researcher wants to identify and analyze the legal considerations of the judge who gave custody to his biological father as a result of the divorce, which should, in accordance with the KHI, the custody of his biological mother. This study uses a qualitative research type whose quality is in accordance with the results of the assessment with an understanding of the analysis. This study is in the form of an analysis of cases related to the delegation of custody of children to their biological fathers, which occurred at the Mempawah Religious Court using the concept of maslahah as an analytical knife. The criteria for the data obtained are primary and secondary data. Data collection techniques used in the form of findings and literature study. The results showed that the transfer of custody of the child to the biological father was because the child's mother was not trustworthy, busy working, minimal economic conditions, and did not have the will to educate children so that since the age of 4 (four) months the child was handed over to Defendant II (his biological mother). ) Defendant I) who has converted to a non-Muslim religion.